Upaya Guru dalam Mengatasi Kesulitan Belajar Membaca Siswa - Fitriyani Maghfiroh; Hani Atus Sholikhah; Fuaddilah Ali Sofyan (JIP Jurnal Ilmiah PGMI, 2019)
As for the background, researchers took this problem because according to researchers that reading is an important aspect of the learning process, especially on the basis for continuing to the next level. The results of this study indicate that. (1) the ability of students to learn to read in class I MIN 1 Ogan Ilir varies in each class but has similarities that are almost the same seen from the results of the percentage of data obtained is almost the same. (2) The teaching and learning process for students who have difficulty learning to read at MIN 1 Ogan Ilir also has differences in the three classes 1 depending on the actions taken by the teacher in the class. (3) Supporting factors and barriers to the efforts of teachers in overcoming difficulties in reading reading in Grade 1 students at MIN 1 Ogan Ilir also have different problems in the three classes, but all of them have almost the same, namely lack of support from the interests of students themselves. (4) The efforts made by the teacher to overcome students' reading difficulties also vary in the three classes of MIN 1 Ogan Ilir where the teacher has his own way to overcome the difficulties experienced by his students. Keywords: effort, teacher, learning difficulties, reading